KAJIAN ANTARA DOSIS PUPUK KANDANG SAPI DAN ASAL TANAH TERHADAP PERTUMBUHAN SAWI PAGODA (Brassica narinosa) - Rahman, Teguh Arif; Widata, Sri; Arnanto, Driska (Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of the research was to determine the interaction between the dose of cow manure and soil origin on the growth of pagoda mustard greens. This research was carried out on the grounds of the Asmadewa Green House, Faculty of Agriculture, Bachelorwiyata Tamansiswa University, Jalan Celeban, Tahunan, Umbulharjo District, Yogyakarta City. The research was carried out from 25 December 2023 to 31 January 2024. This research used a 3x3 factorial experimental method using a Completely Randomized Design (CRD), with 2 treatment factors, namely: concentration of cow manure and time of application of soil types. Data analysis using variance to determine the treatment of variables was then continued using Duncan's Multiple Range Test (DMRT). The parameters observed were plant height, number of leaves, leaf width, leaf length, dry weight and wet weight of pagoda mustard plants. The results of the research revealed that the treatment of giving doses of cow manure and soil type showed no interaction with the growth variables of pagoda mustard plants. Treatment with soil type did not show any significant difference in the growth of pagoda mustard greens. The treatment with doses of cow manure showed no significant difference to the growth of pagoda mustard greens